A Portable Optical Fiber Sensing Platform Based on Fluorescent Carbon Dots for Real‐Time pH Detection. Issue 4 (23rd December 2021) - Cai, Yi; Wang, Minghao; Liu, Mengxian; Zhang, Jing; Zhao, Yong
Abstract: An optical fiber sensing platform based on the nitrogen‐doped carbon dots (N‐CDs) for online detection of pH value in real time has been developed. The pH‐sensitive N‐CDs are synthesized by a one‐pot hydrothermal method. To compose the sensing probe, the N‐CDs are immobilized on the surface of the fiber tip by the biocompatible hydrogel. According to the results of optical simulation, the fiber tip is designed to be tapered for efficient excitation and fluorescence collection. The assembling process of the sensing probe can be accomplished by the method of in‐situ polymerization without any mold in seconds. The fluorescence of the sensing probe can be enhanced or quenched by pH value variation in a certain range and transmits to the spectrometer. The maximum diameter of the proposed sensing probe is only 450 µ m. Therefore, the sensing platform with rapid response has great potential application for remote monitoring in the narrow space. Besides, the proposed platform is portable and provides a new photonic‐sensing method for emergency analysis. Abstract : An optical fiber sensing platform based on the nitrogen‐doped carbon dots for online detection of pH value in real time is developed. The sensing probe with a maximum diameter of 450 µm can be assembled by the method of in‐situ polymerization in only 10 s. The linear pH value response can be obtained in the range of 2.00–3.92 and 8.00–13.02, respectively.